Análisis de la tradición “Historia de un cañoncito” de Ricardo Palma - Sifuentes Peláez, Juana Elvia (2019)
In this work report on professional proficiency, a learning session has been designed and implemented on the analysis of one Ricardo Palma's traditions, “Historia de un cañoncito”, aimed at working with children in the second grade of secondary education. It has been attempted that the learning activity be the most dynamic and productive, for which an active and participatory methodology has been considered. The corresponding scientific and pedagogical support that support the work to be carried out in the classroom is attached.